EXPRESSIVE SYNTACTIC STRUCTURES IN M.E. SALTYKOV-SHCHEDRIN’S ARTISTIC DISCOURSE - A. Chupryakova, Olga; S. Safonova, Svetlana; T. Abikenov, Mukhit (Gênero & Direito, 2019)
The article is dedicated to the research of expressive syntactic structures in M.E. Saltykov-Shchedrin’s artistic discourse that received major or minor types and phraseological statuses. By strikingly combining and synthesizing real and fictional things, writer reaches the heights of satirical imagery. It should be noted that, judging by the satirical nature of his works, the intensity semantics (exaggeration or hyperbole) carries a strong importance, while the wide specter of hypotaxis-based sentences is used as a means of its realization. Syntactic units of idiomatic structure that express intensity-consequential, concession-amplification, temporal-concession and other relations are differentiated by their semantic diversity, merging of informative and connotative meanings, combination of real and surreal contents, combination of stable and variable components. The expressions created by the tak/takoj/nastol’ko/do togo/do takoj stepeni…chto; slishkom/chereschur…chtoby; chto (by) ni/kak (by) ni…a; uzh na chto…a; ne uspeet…a (kak); eshche ne..., a uzh scheme are related to the phrase models mentioned above. They are formed on the base of constant components that make up sentence’s carcass, which provides free lexical filling. Meanwhile, the sphere of relational meanings is complicated by the modus-expressive meanings. Semantics of contrast, unusualness, suddenness (subjective hyperbolization that does not match the objective state of affairs, combining of incompatible, shift of moral orientations, combination of real and potential plans etc.) contributes to the appearance of the comical or sarcastic effect. In the functional and textual aspect, the analyzed phrase models become the leading means of presenting speaker’s position in the comprehension of world’s moral picture